Optimal design of hydrogen‐blended natural gas pipeline network considering separation systems - Gu, Shiya; Bai, Yunhai; Dong, Yachao; Du, Jian (AIChE journal, 2025)
Blending hydrogen into existing natural gas pipelines is considered the most feasible choice for long‐distance, large‐scale hydrogen transportation in the early stage of hydrogen economy development. To integrate the optimization of hydrogen‐blended natural gas pipeline network and subsequent hydrogen/natural gas separation process, this article presents a mixed‐integer nonlinear programming model, aiming to minimize the total annual project net cost. To tackle the computational complexity resulting from the large‐scale and nonlinear nature of practical design problems, a decomposition algorithm is tailored to the proposed model. Two case studies demonstrate that compared to stepwise model, the proposed pipeline‐separation integrated model offers economic benefits and practical value, incorporating separation processes and satisfying constraints of hydrogen demand, pressure and blending ratio requirements, which achieves an economically optimal design for both pipeline transportation and separation systems, and provides a viable solution for the broader application of hydrogen‐blended natural gas networks.